2018
DOI: 10.1038/s41380-018-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of attention deficit hyperactivity disorder

Abstract: Decades of research show that genes play an vital role in the etiology of attention deficit hyperactivity disorder (ADHD) and its comorbidity with other disorders. Family, twin, and adoption studies show that ADHD runs in families. ADHD's high heritability of 74% motivated the search for ADHD susceptibility genes. Genetic linkage studies show that the effects of DNA risk variants on ADHD must, individually, be very small. Genome-wide association studies (GWAS) have implicated several genetic loci at the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
568
1
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 782 publications
(600 citation statements)
references
References 175 publications
9
568
1
22
Order By: Relevance
“…Brainimaging studies have identified various different regions, such as the cerebellum and frontal cortex, to be implicated in ADHD 3,4 . Twin studies have estimated the narrow-sense heritability of ADHD to be approximately 70%, suggesting a strong genetic component is driving the phenotypic variance 5 . Recently, a large-scale genome-wide association study (GWAS) identified several loci that were significantly associated with ADHD 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Brainimaging studies have identified various different regions, such as the cerebellum and frontal cortex, to be implicated in ADHD 3,4 . Twin studies have estimated the narrow-sense heritability of ADHD to be approximately 70%, suggesting a strong genetic component is driving the phenotypic variance 5 . Recently, a large-scale genome-wide association study (GWAS) identified several loci that were significantly associated with ADHD 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Family-genetic studies indicate that ADHD aggregates in families, with a 5-8 fold increased risk in first-degree relatives and a 2-fold increased risk in second-degree relatives (Faraone et al, 1994). Twin studies found evidence for a narrow additive heritability of 0.75 to 0.91 which was robust across familial relationships and across definitions of ADHD as the end of a continuum or as a disorder with various symptom cutoffs (Levy et al, 1997;Sherman et al, 1997).…”
Section: Behavior-genetic Studiesmentioning
confidence: 70%
“…ADHD is a multifactorial disorder with heritability averaging 76% throughout the lifespan [3][4][5] . There is consistent evidence that both common and rare variants make an important contribution to the risk for the disorder [6][7][8][9][10][11] . Several genome-wide association studies (GWAS) and meta-analyses across those have been conducted 7 , but only the largest GWAS meta-analysis (GWAS-MA) performed to date, including 20,183 ADHD patients and 35,191 controls, reported genome-wide significant loci (N=12) 6 .…”
Section: Introductionmentioning
confidence: 96%